Assessment of Tertiary Education Trust Fund (TETFund) Interventions and Academic Staff Job Performance in Public Universities in Southwest, Nigeria - Christianah , Aina; Olufunmilola, Olorunsola (American Journal of Education and Practice, 2023)
Purpose: The study assessed TETfund interventions and academic staff job performance in public universities in Southwest, Nigeria. This was by considering the provision, adequacy and accessibility to physical infrastructure and instructional material by academic staff in public universities. Methodology: Descriptive survey research design was adopted for the study. The population consisted of 11864 Nigeria public universities academic staff. Nine hundred and twenty-seven (927) lecturers, including Heads of Departments (HODs) formed the sample. Two sets of research instruments were designed for the study; tagged TETFUND Interventions Questionnaire (TIQ) for lecturers; and Academic Staff Job Performance Questionnaire (ASJPQ) for H.O.Ds. The instruments were validated by experts and the reliability of the instruments was also ensured using Test-re-test method. Coefficients of 0.86 and 0.87 were obtained for TIQ and ASJPQ respectively. All hypotheses were tested at 0.05 level of significance. Research questions were answered using frequency counts, mean and standard deviation. The hypotheses were tested using Pearson Product Moment Coefficient. Findings: The results revealed that there was a positive, high and significant relationship between physical infrastructure, instructional materials and academic staff job performance. The study concluded that, though TETFund might not have been able to meet all the needs of academic staff, it has to a very high extent positively improved their job performance in terms of physical infrastructures and instructional materials. Recommendations: It was therefore recommended that the tempo in the area of physical infrastructure and instructional materials should be intensified and sustained since these structures and facilities significantly contributed to the quality of teaching and research engagements that take place in the university system. The federal government should also increase the percentage of revenue allocated to TETfund for procuring more instructional materials and execution of more infrastructural projects which should be enough to accommodate the students' enrolment in Nigeria public universities.